Sub-critical water extraction of fucoidan from brown algae Padina sp. - Rosdi, Anis Nurdhiani (2021)
Chemical, mechanical, and biological approaches are the common extraction techniques used to extract bioactive compounds. These techniques use chemical solvents, have long processing steps, and produce low yields. An important aspect being considered in extracting bioactive compounds is fast extraction techniques and environmentally friendly extraction processes. One of the emerging green extraction processes is called Subcritical Water (Sub-CW) Extraction. The advantages of this technique include significant reduction of solvents, non-toxic green solvent (water), higher extraction yields, less extraction time, and low costs of extracting agents. This study investigates the extraction of fucoidan compounds in brown algae using Sub-CW technology. The study covers screening and optimizing Sub-CW parameters, evaluating the process kinetics and thermodynamics, and comparing the yield of fucoidan with the conventional methods. The presence of fucoidan was confirmed by running the standard fucoidan using high performance liquid chromatography (HPLC), and the biomass was further analyzed using standard analytical instruments. Several analyses have been done to support the HPLC results. The samples were characterized with Fouriertransform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and elemental analyzer CHNS to identify the -SO3H functional group and other organic compounds, surface morphology, and elemental analysis accordingly. The effect of three different variables, which were temperature, reaction time, and biomass concentration, were investigated according to a single factor to achieve maximum fucoidan yield. The result showed that the highest extraction yield was achieved at 180°C, 10 min extraction, and 2 % biomass concentration. In the optimization study, the Sub-CW was carried out based on the data generated from central composite design (CCD) by varying different process parameters, including reaction temperature, reaction time, and biomass concentration. The experimental range and levels of the independent process variable were set based on the parameters from the screening experiment. The optimum fucoidan of 50.65 wt% was achieved at 176 °C,12 min, and a concentration of 2%. A single, consecutive reaction model used for data validation showed a good agreement between the experimental and theoretical data generated. In terms of the kinetic and thermodynamic behavior of fucoidan extraction from brown algae by Sub-CW, it was observed that the fucoidan yield could be rapidly produced and decomposed from the subcritical water extraction process. Thermodynamic analysis by transition-state theory showed the subcritical water reaction process as endothermic, while the Gibbs free energy of activation showed the reaction as non-spontaneous, requiring constant external energy to support it. Overall, this study shows the capability of Sub-CW in extracting fucoidan from brown algae. Thus, the findings will benefit the food and pharmaceutical industries to utilize a green method for extracting biomolecules from macroalgae for new products with high added value.